(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
Development in technologies and new research in multiple disciplines lead to ever-changing world. Same is the case with information technology and education system. Previous developments in ICT have made the universities smart due to enhancements in digital communications and advanced learning techniques with multi-media and internet. But, now the time comes for knowledge technology. This technology can completely change the ways of teaching and learning. This paper discusses how cognitive computing in combination big data can provide a new paradigm called smarter university model. First, smart university model is discussed and analysed. Based on this analysis and big data exploitation as well as cognitive computing with IOT, a new paradigm in education is proposed. This paradigm also fulfils the needs of industry and labour market. So, it demands a major blend in curriculums of their courses in different disciplines and also new multi skilled persons with new designations in industry.